1978
DOI: 10.1051/jphys:0197800390110121500
|View full text |Cite
|
Sign up to set email alerts
|

Examen des paramètres de l'Hamiltonien de spin de Mn2+ substitué a M, dans les fluoperovskites AMF3, dans la phase tétragonale de RbCaF3 et dans les composés A2MF4

Abstract: 2014 Nous confrontons les divers mécanismes qui ont été proposés pour rendre compte des levées de dégénérescence en champ nul des niveaux de spin de Mn2+ et le principe de superposition aux résultats expérimentaux obtenus dans la série cubique AMF3, dans la phase tétragonale de RbCaF3, où le site de l'ion Mn2+ est très faiblement distordu, et dans les composés quadratiques A2MF4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In the same vein as for octahedral NiF 6 4– , MnF 6 4– , or FeF 6 3– units in cubic fluoroperovskites, , both A s and q s quantities, corresponding to the e g (σ) orbital, are strongly dependent upon the metal–ligand distance, while A p is much less sensitive.…”
Section: Resultsmentioning
confidence: 79%
“…In the same vein as for octahedral NiF 6 4– , MnF 6 4– , or FeF 6 3– units in cubic fluoroperovskites, , both A s and q s quantities, corresponding to the e g (σ) orbital, are strongly dependent upon the metal–ligand distance, while A p is much less sensitive.…”
Section: Resultsmentioning
confidence: 79%
“…In the case of substitutional Mn2' impurities in the fluoride lattices with cubic or nearly cubic local symmetries it has been shown that A, is rather sensitive to the host lattice [12]. The origin of the sensitivity has been explained through the strong dependence of A, upon the equilibrium impurity-ligand distance R [13].…”
Section: Comments On the Isotropic Superhyperfine Constant A For Fe3mentioning
confidence: 97%
“…Mn 2+ -doped cubic fluoroperovskites are model systems whose equilibrium impurityligand distance, R 0 , has been explored by different methods [5][6][7]12]. However, there are several important questions which need to be clarified:…”
Section: Introductionmentioning
confidence: 99%
“…The present work is aimed at exploring the local structure and optical and vibrational properties associated with Mn 2+ impurities in cubic AMF 3 fluoroperovskites [4][5][6][7][8][9][10][11][12][13][14] by means of a recent method for improving the embedding in the realm of the density functional theory (DFT) [15][16][17]. In this method the electronic density of a finite cluster is divided into two regions.…”
Section: Introductionmentioning
confidence: 99%